PWE-047 Bowel resections for inflammatory bowel disease in nhs tayside, scotland: a retrospective study. (22nd June 2015) - Livie, J; Walsh, S; Ziyaie, D; Groome, M; Todd, J; Reynolds, N; Mowat, C
Abstract : Introduction: NHS Tayside serves a population of 400, 000, with 2 acute hospitals providing emergency and elective surgery. The Inflammatory Bowel Disease (IBD) service cares for approximately 2000 patients. At present, there is no detailed record of the number of bowel resections performed locally for IBD. We retrospectively reviewed the number of operations performed over a 6 year period. Method: Caldicott Guardian approval was granted. The Pathology Dept. archives were searched using SNOMED codes to generate a list of patients undergoing bowel resection between 1 st January 2008 and 31 st December 2013. The patient–s CHI number was used to search the electronic patient record to view pathology reports, clinical letters and paper casenotes if required. Verified resections for Crohns Disease (CD), Ulcerative Colitis (UC), Indeterminate Colitis (IC) had details about the resection recorded; elective vs emergency, open vs laparoscopic, and the operating surgeon was noted. Results: Over the study period there were 307 resections in 263 patients, with a mean of 51 resections/yr (median 50.5). The proportions of elective and laparoscopic procedures increased over time from 50% to 58% and 16% to 34% respectively. 182 resections (165 patients) were for CD, 114 resections (89 patients) for UC, and 11 resections (9 patients) were classified as IC. Of the resections for CD; 59% were female, median age 38 (IQ range 25–55). 91/182 procedures were emergency, and 140/182 were open. The number of resections/yr for CD decreased over time, peaking at 37 in 2009, falling to 27 in 2013. Of the resections for UC; 55% were male, median age 49.5 yrs (IQ range 31–65). 45/114 were emergency, and 74/114 were open. The median number of resections/yr was 18.5, with peaks of 25, 24 in 2010, 2013 respectively. Colorectal surgeons accounted for 10/16 operators performing elective surgery and undertook 96% of resections, compared to 12/29 and 70% for emergency surgery. Over the study period, the median number of emergency resections per surgeon was: 7.5 (range 3–22) and 2 (range 1–5) for colorectal and non-colorectal respectively. For elective surgery the median was 8 (range 4–45) per colorectal surgeon. Conclusion: In NHS Tayside, the trend is towards more elective, laparoscopic surgery for IBD. The number of resections/yr for CD is falling. Elective surgery is almost exclusively performed by colorectal surgeons, and the majority delivered by a small group. 30% of emergency resections are performed by non-colorectal surgeons who resect IBD infrequently. Disclosure of interest: None Declared.